PENINGKATAN MUTU LITERASI PENDIDIKAN DAN PONDOK BACA DESA OMBUL KECAMATAN AROSBAYA- BANGKALAN - Wahyudi, Mohammad Arief; Firmansyah, Ihwan (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Ombul is the name of village which is located in the Arosbaya- Bangkalan Madura sub-district. The people in the village of Ombul have a livelihood by farming, traders, porters and overseas migrants (TKI). Community awareness about children's education is very lacking, this is due to the lack of information on technology from outside which is very minimal. The lack of motivation that exists in every family is very influential, especially the family environment and the surrounding community. Therefore, we, as PKM proponents, are planning a work program, namely Tutoring and Reading Cottages which synergize with the village administration and nearby schools to help people who have children to become students to participate in the program. With this work program, it is hoped that the village community will be able to better understand and increase self-awareness of the importance of education. The results achieved are: 1) increasing the ability to learn a material according to the level of education; 2) have the ability to read a sentence and 3) assistance is still needed so that it can develop and be followed up by partners with the closest school